Effects of Sugarcane and Soybean Intercropping on the Nitrogen-Fixing Bacterial Community in the Rhizosphere - Liu, Yue; Ma, Wenqing; He, Hongliang; Wang, Ziting; Cao, Yanhong (Frontiers in Microbiology, 2021)
Intercropping between sugarcane and soybean is widely used to increase crop yield and promote the sustainable development of the sugarcane industry. However, our comprehend of the soil microenvironment in intercropping systems, especially the effect of crop varieties on rhizosphere soil bacterial communities, is still poor. We selected two excellent sugarcane cultivars, ZZ1 and ZZ9, from Guangxi and the local soybean variety GUIZAO2 from Guangxi for field interplanting experiments, these two cultivars of sugarcane were proved to have good drought resistance. Rhizosphere soil samples were collected from the two intercropping systems to measure, physicochemical properties and soil enzyme activities and to extract total soil DNA for high-throughput sequencing. We found that the diversity of the rhizosphere bacterial community was significantly different between the two intercropping systems. The ZZ9 intercropping system enriched the nitrogen-fixing bacteria more than ZZ1, which increased available nitrogen in the soil. In addition, ZZ9 intercropping with soybean formed a more compact rhizosphere environment than ZZ1, thus providing favorable conditions for sugarcane growth. These results provide guidance for the sugarcane industry, especially for the management of sugarcane and soybean intercropping in Guangxi, China.